The World Bank’s Assistance Strategies for Brazil from a political perspective (1990-2020) (Tempo e Argumento, 2022)
This article analyzes the World Bank’s assistance strategies for Brazil in the period from 1990 to 2020, in order to evidence the strategic importance attributed to fiscal austerity and neoliberal reforms, evaluate how the “assault on poverty” was used as rhetoric and a legitimation mechanism for the neoliberal agenda, problematize the World Bank’s relationship with the private sector and civil society organizations which are "partners" of the institution and, finally, discuss the decisive importance of the Bank’s advisory and consultancy services in the country. Assistance strategies constitute the most important documentation in the World Bank’s relations with Brazil. The analysis focuses on the periods from 1990 to 2002 (the Collor, Itamar and FHC administrations), from 2003 to 2016 (the Lula and Dilma administrations) and from 2016 to 2020 (the Temer and Bolsonaro administrations). The paper shows that the modus operandi of the World Bank combined funding with advisory services, technical assistance, and economic research, in order to disseminate advice and practices related to what governments should do and how they should do this in public policy questions. It is argued that Brazil’s relations with the World Bank were more programmatic or more pragmatic depending on the government, but always involved the choices of national agents over the directions to follow and how to do this in the question of development. It is evidenced that for thirty years the fiscal adjustment assumed a normative primacy in the Bank’s agenda, in the sense of preceding and framing all and any discussion about the directions and means of development.
Keywords: fiscal austerity; economic liberalization; structural adjustment; state reform; the World Bank